Professional issues in IT - Bott, Frank; Taylor, Neil (BCS, The Chartered Institute for IT, 2022)
Relevant to all sizes of organisation, this book addresses the social, legal, financial, organisational and ethical issues faced by IT professionals, in alignment with the BCS HEQ 'Diploma in IT' core module: Professional Issues in Information Systems Practice. This new edition takes into account the social and legal implications of the changes to legislation and technology over recent years, including the GDPR and Data Protection Act, health and safety, and the impact of IT on the environment.
"BCS Learning & Development Limited". - Law and GovernmentThe Computing ProfessionWhat is an Organisation?Structure and Management of OrganisationsFinancing a Start-Up CompanyFinancial AccountingManagement AccountingInvestment AppraisalHuman Resources IssuesDiversity, Inclusivity and EqualityIntellectual Property RightsSoftware Contracts and LicensesData Protection, Privacy and Freedom of InformationInternet IssuesComputer Misuse . - Includes bibliographical references and index. - Online resource; title from title details screen (O'Reilly, viewed August 29, 2022)
Keywords: Information technology -- Vocational guidance; Information technology -- Management; Technologie de l'information; Orientation professionnelle; Technologie de l'information; Gestion; Computing: general; Computing & information technology; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Organizational Behavior; Information technology; Management; Information technology; Vocational guidance; Information technology: general topics; Computing and Information Technology; Education & general interest